PENGARUH ENTREPRENEURIAL MINDSET TERHADAP MINAT BERWIRAUSAHA DAN IMPLIKASINYA TERHADAP KEPUTUSAN BERWIRAUSAHA - Ramdani, Gilang; Sadiah, Ati; Srigustini, Astri (Transpublika Publisher, 2023)
The research aims to assess the impact of Entrepreneurial Mindset on Interest in Entrepreneurship and the subsequent implications for Entrepreneurial Decisions. The research methodology employs a survey approach with a descriptive design. The targeted population comprises students from Siliwangi University FKIP, who belong to the 2019-2022 batch, totaling 6,700 individuals. Non-probability sampling, specifically the purposive sampling technique, was used to select a sample size of 376 participants based on the researcher's considerations. Questionnaires were utilized for data collection, and path analysis was employed as the statistical method, encompassing both direct and indirect hypotheses. The study's findings reveal the following: 1) Direct hypothesis calculations indicate that Entrepreneurial Mindset significantly influences Entrepreneurial Decisions, as well as Entrepreneurial Mindset's impact on interest in entrepreneurship and interest in entrepreneurship on entrepreneurial decisions. 2) Indirect hypothesis calculations demonstrate that Entrepreneurial Mindset indirectly influences entrepreneurial decisions through its effect on interest in entrepreneurship.